Comparison of the inverted internal limiting membrane flap technique without versus with an autologous blood clot for treating macular hole-associated retinal detachment - Ke Zhu; Yingchao Wang; Boya Lei; Ling Chen; Yanqiong Zhang; Qing Chang; Gezhi Xu; Yingqin Ni (Eye and Vision)
Abstract Background To investigate the anatomical and functional outcomes of macular hole-associated retinal detachment (MHRD) after vitrectomy using the inverted internal limiting membrane (ILM) flap technique with autologous blood clot (ABC). Methods This retrospective observational study included 80 eyes with MHRD that underwent vitrectomy with ILM flap without (46 eyes) or with ABC (34 eyes). Fundus photography and optical coherence tomography were evaluated. The pre- and postoperative best-corrected visual acuities (BCVAs) and BCVA improvement were compared between the two groups. Results The MH closure rates after initial surgery were similar in the ILM flap group and ILM flap with ABC group [40 (87%) vs. 29 (85%) eyes, respectively]. The proportion of eyes with hyperreflective bridging tissue (HBT) was lower in the ILM flap group than ILM flap with ABC group [13 (32%) vs. 16 (55%) eyes, P = 0.060]. The postoperative improvement in BCVA was significantly better in the ILM flap group (P = 0.027). Multiple linear regression analysis revealed that preoperative BCVA was positively associated with postoperative improvement in BCVA (β = 0.638, P = 0.000), while the ILM flap with ABC technique was negatively associated with postoperative improvement in BCVA (β =  − 0.299, P = 0.039, adjusted r2 = 0.415). Conclusions The inverted ILM flap technique alone resulted in better foveal configurations and visual outcomes than the ILM flap technique combined with ABC in patients with MHRD.